Dental Implants: Prevalence, Association with Periodontal Diseases and Awareness of Oral Hygiene among Dental Implant Patients in Saudi Arabia: A Cross-Sectional Study - Amal Abushal; Malak Alqudsi; Nujood Alahmadi; Mohammed Almalsi; Haifa Alharbi; Eman Anaim; Manal Murad; Abousada, Huda (International Journal of Innovative Research in Medical Science, 2020)
Periodontal disease is a broad spectrum that involves different entities and severity levels of the disease. Dental implants, just like normal teeth, can be affected by periodontal disease. This descriptive questionnaire-based study provides a brief shot on the most prevalent periodontal diseases associated with dental implants, associated risk factors, and levels of understanding and awareness about oral hygiene in the Saudi population. Results concluded that 10.5% of population have dental implants. 28.5% the sample confirmed that they have some sort of periodontal disease. Most prevalent symptoms among patients with dental implants are in order: periodontal pockets, redness and blood spitting after tooth brushing, and finally gingival recession. Most associated co-morbidities are cardiovascular disease and diabetes mellitus. Regarding oral hygiene, through assessing two oral health concepts: twice daily tooth brushing, and balanced diet, it is found that more than half of the sample (51.3%) apply these two concepts in their life, while the rest of the sample misses one or both of these two concepts. Focus should be directed toward raising the public awareness about periodontal disease and its symptoms, especially in cases of dental implants, and raising understanding and awareness about different oral health concepts.